Integrated Pathologic Score Effectively Stratifies Patients With Pancreatic Ductal Adenocarcinoma Who Received Neoadjuvant Therapy and Pancreaticoduodenectomy. (6th April 2023) - Sohn, Aaron J.; Taherian, Mehran; Katz, Matthew H.G.; Prakash, Laura R.; Chatterjee, Deyali; Wang, Hua; Kim, Michael; Tzeng, Ching-Wei D.; Lee, Jeffrey E.; Ikoma, Naruhiko; Rashid, Asif; Wolff, Robert A.; et al.
Abstract : Neoadjuvant therapy is increasingly used to treat patients with pancreatic ductal adenocarcinoma (PDAC). Pathologic parameters of treated PDAC, including tumor (ypT) and lymph node (ypN) stage, and tumor response grading (TRG) are important prognostic factors in this group of patients. To our knowledge, a multifactorial prognostic score combining pathologic features including ypT, ypN, and TRG in treated PDAC patients has not been reported. Our cohort consisted of 398 PDAC patients who received neoadjuvant therapy and underwent pancreaticoduodenectomy at our institution. All pancreaticoduodenectomy specimens were grossly and microscopically evaluated using a standard protocol. The integrated pathologic score (IPS) was calculated as the sum of the scores for ypT, ypN, and TRG according to either the MD Anderson grading system (IPSMDA) or the College of American Pathologists (CAP) grading system (IPSCAP). The IPSMDA and IPSCAP were correlated with clinicopathologic parameters and patient survival. Using either IPSMDA or IPSCAP, PDAC patients were stratified into 3 distinct prognostic groups for both disease-free survival (DFS) ( P <0.001) and overall survival (OS) ( P <0.001). The IPSMDA and IPSCAP correlated with tumor differentiation, margin status, the American Joint Committee on Cancer (AJCC) stage, and tumor recurrence ( P <0.05). In multivariate analysis, IPSMDA, IPSCAP, margin status, and tumor differentiation were independent prognostic factors for both DFS ( P <0.05) and OS ( P <0.05). However, patients with AJCC stage IB, IIA, or IIB disease had no significant difference in either DFS or OS ( P >0.05). The IPS appears to provide improved prognostic information compared with AJCC staging for preoperatively treated patients with PDAC.